PENGEMBANGAN MODEL PELATIHAN KEPALA SEKOLAH BERBASIS SEULANGKE UNTUK PENINGKATAN KOMPETENSI RISK-TAKING DAN LEGITIMASI KULTURAL DI ACEH BESAR - Maidar, Maidar; M. Daud, Yusri; Al-Ghifary, Farhan (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2025)
The leadership competence gap in Indonesia, particularly Aceh (UKKS score 53.89), stems from the dysfunction of conventional training. Previous training fails to incorporate futuristic competencies (risk-taking, negotiation) and neglects cultural legitimacy, resulting in a significant execution gap. This study aims to develop and validate the Seulangke-Based School Principal Training Model to bridge this gap through the lens of Sociocultural Theory. Utilizing the R&D ADDIE Model methodology and a Quasi-Experimental design (N=27), the research operationalizes the local Acehnese wisdom, Seulangke (wise, dignified, negotiator), as a cultural tool to mediate competence internalization. The developed model proved Highly Valid (mean score 4.64–4.71) and Highly Practical (85.9%). The effectiveness test demonstrated a significant improvement in competence for the Experimental Group, yielding an N-Gain Score of 0.649 (Medium-to-High category). This increase, particularly in Futuristic Competencies, was strongly confirmed by the $T$-Test (p < 0.05). The findings empirically validate that the Seulangke Model successfully fosters moral authority, which is crucial for internalizing managerial practices and overcoming the educational leadership execution gap.